2020
DOI: 10.7759/cureus.10254
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Glycolyzed Hemoglobin A1c and Hearing Loss in Diabetic Patients

Abstract: Our study aimed to determine the correlation between glycated hemoglobin (HbA1c) levels and the audiometric parameters in diabetic patients. Methods We included 724 patients (376 male, 348 female) in our outpatient clinic and created four groups by reference to the HbA1c values. The first group was 192 patients with an HbA1c value < 4.5, 176 patients with an HbA1c value between 4.5-5 as Group 2, 177 patients with an HbA1c value between 5-6 as Group 3, and 179 patients that had an HbA1c value greater than 6 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…On the other hand, patients with T2DM exhibited a higher risk of hearing impairment and incidental hearing loss [11][12][13]. The present study found that almost one-third of the patients had a moderate-to-severe hearing impairment.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…On the other hand, patients with T2DM exhibited a higher risk of hearing impairment and incidental hearing loss [11][12][13]. The present study found that almost one-third of the patients had a moderate-to-severe hearing impairment.…”
Section: Discussionsupporting
confidence: 41%
“…Previous observational studies have linked T2DM and hearing impairment, though the current data are controversial [9,10]. Patients with T2DM exhibited a higher risk of hearing impairment and incidental hearing loss [9,[11][12][13]. Nonetheless, the exact pathogenic mechanism by which T2DM affects the vestibular and auditory systems has not been fully understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…Findings of current research was comparable to the previous studies. [19,20] In group I 18 (45%) patients were smokers and in group II 15 (27.5%) were smokers. [21] As a result of microvascular problems, the high-frequency specific regions of the cochlea may be more sensitive to ischemia alterations [22] resulting in diabetes-related hearing loss.…”
Section: Discussionmentioning
confidence: 94%
“…Cardiovascular factors, such as dyslipidemia and hypertension, have a complex association with noise exposure and hearing loss; however, studies are inconsistent and oftentimes contradictory . The microvascular consequences of diabetes include hearing loss, with known associations between hyperglycemia and glycohemoglobin levels with hearing loss . Other metabolic factors that may be associated with the ramifications of stress, such as body mass index, have also shown similar associations with hearing loss .…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] The microvascular conse- quences of diabetes include hearing loss, with known associations between hyperglycemia and glycohemoglobin levels with hearing loss. [44][45][46] Other metabolic factors that may be associated with the ramifications of stress, such as body mass index, have also shown similar associations with hearing loss. 47 Lastly, systemic inflammatory biomarkers, including C-reactive protein levels, have an unclear association with hearing, with associations noted only stratifying by age.…”
Section: Discussionmentioning
confidence: 99%